The United States- Argentina honey case and the case against antidumping laws - Luzi, Nora C. (2004)
The failure of the Fifth Ministerial Conference in Cancun2 was not only a setback for the Doha Round, but also for the World Trade Organization’s efforts to enhance international trade as means to growth and development. The group of developing countries led by Brazil, China, India and South Africa, known as G-22, made the first step towards a new balance in the multilateral trading system. Agriculture was considered a key issue if the new Round was meant to succeed. It will certainly take time and a great deal of political will to get countries back to the negotiating table, but the benefits will outweigh the costs. Substantial poverty reduction in the world will be achieved by tackling agricultural protection. Poor countries mainly produce agricultural products and intensive labor products such as textiles usually facing protective – developed markets. Subsidies in the OECD account for more than US$ 300,000 million targeted at agricultural products originatingin developing countries. Annual subsidies at the OECD are equivalent to six times the direct economic aid those countries provide for the poor countries.3 Developing countries are responsible for seriously committing themselves and reducing agricultural barriers – tariff and non- tariff – in order to facilitate trade liberalization towards an equity free trade world. Párrafo extraído del texto a modo de resumen